Higher Order Thinking Skill’s Instruction Delivered by EFL Teacher During an Online Learning - Nazelya Puspita Kencana (Department of English Language Education, UIN Sunan Ampel Surabaya, 2023)
HOTS promote the idea of assessing students’ critical thinking, creative thinking, and problem solving. Many teachers claimed to implement HOTS in the classroom, but turned out they tended to have LOTS in their teaching and learning process. Since the teaching and learning process has shifted from in person meeting to the virtual one due to COVID-19, there was an adjustment to conduct the learning process. Hence, the present study aimed to figure out teacher’s strategies to deliver HOTS’ instruction, students’ HOTS, and the construction of HOTS’ instruction during online learning. This study employed qualitative research and two English teachers were involved. The data was gathered through classroom observation. The findings revealed that direct instruction and questioning strategies were efficient and effective to activate students’ HOTS through asking the students’ point of views about online and offline learning systems and having the students’ work in group to discuss a certain topic. Further, analyzing and evaluating procedural knowledge and metacognitive knowledge were the most abilities exposed by the instructions. In this case, the students activated their critical thinking, creative thinking during online learning. Then, the instructions delivered by the teachers during the class promoted students’ creative thinking and critical thinking because they encouraged students’ creativity, motivated their self-confidence to participate in the class, had the students be communicative, and exposed students’ understanding and knowledge. The instructions were clear enough and reflected imperative and interrogative sentences, so that the students easily understood what they needed to do during the learning process. However, one teacher could not promote HOTS pretty well because he encouraged the students to talk about direct and indirect speech, which was the area about understanding conceptual knowledge.